Improving infant outcome with a 10 min Apgar of 0. Issue 2 (23rd October 2014) - Kasdorf, Ericalyn; Laptook, Abbot; Azzopardi, Dennis; Jacobs, Susan; Perlman, Jeffrey M
Abstract : Objective: Asystole at birth and extending through 10 min is rare, with current international recommendations stating it may be appropriate to consider discontinuation of resuscitation in this clinical scenario. These recommendations are based on small case series of both term and preterm infants, where death or abnormal outcome was nearly universal. Study objective was to determine recent outcome of infants with an Apgar score of 0 at 10 min despite cardiopulmonary resuscitation, treated with therapeutic hypothermia or standard treatment, in randomised cooling studies. Design: Outcome studies of infants with an Apgar of 0 at 10 min subsequently resuscitated and treated with hypothermia or standard treatment were reviewed and combined with local outcome data of infants treated with hypothermia. Results: Four recent studies (n=81) and local data (n=9) yielded a total of 90 infants with an Apgar of 0 at 10 min, with 56 treated with hypothermia and 34 controls. Primary outcome of death or abnormal neurodevelopmental outcome (18–24 months) occurred in 73% cooled and 79.5% normothermic infants (p=0.61). Implications: Although poor, the outcome for infants with an Apgar of 0 at 10 min of life has improved substantially in recent years. This may be related to treatment with hypothermia, enhanced resuscitation techniques and/or other supportive management. Current recommendations to consider discontinuation of resuscitation without a detectable heart rate at 10 min should consider these findings.